Akibat Hukum Putusan Mahkamah Agung Nomor 50 P/HUM/2018 Terhadap Syarat Pengangkatan Notaris - Rian Rivaldo (Faculty of Law Universitas Islam Indonesia, 2022)
The issues raised in this article are first, examination on the reasons for the Minister of Law and Human Rights to issue a Regulation of the Minister of Law and Human Rights Number 25 of 2017 on the Notary Appointment Examination; second, review on the Supreme Court's consideration in canceling the Regulation of the Minister of Law and Human Rights Number 25 of 2007 on the Notary Appointment Examination; and third, review on the juridical implications of the Supreme Court's decision Number 50 P/HUM/2018 on the Notary Appointment Examination. This is a normative legal research which is analyzed using a qualitative descriptive method. The results of this study conclude that first, the Minister of Law and Human Rights received a report from the Notary Honorary Council regarding the number of summons to Notaries and requests for minute of the deed by the police, hence a Notary Appointment Examination is required. Second, the Supreme Court canceled the Notary Appointment Examination due to the requirements for passing the Notary Appointment Examination were contrary to higher laws and regulations. Third, the Minister of Law and Human Rights revoked the provisions regarding the Notary Appointment Examination and replaced it with another mechanism, namely Notary Quality Improvement Training (PPKJN)Key Word: Notary Appointment Examination, Right of Judicial Review, Notary Appointment Requirements AbstrakPermasalahan yang diangkat dalam artikel ini, yaitu pertama, mengkaji alasan Menteri Hukum dan Hak Asasi Manusia mengeluarkan Peraturan Menteri Hukum dan Hak Asasi Manusia Nomor 25 Tahun 2017 tentang Ujian Pengangkatan Notaris. Kedua, mengkaji pertimbangan Mahkamah Agung membatalkan Peraturan Menteri Hukum dan Hak Asasi Manusia Nomor 25 Tahun 2007 tentang Ujian Pengangkatan Notaris, dan ketiga, mengkaji implikasi yuridis putusan Mahkamah Agung Nomor 50 P/HUM/2018 terhadap Ujian Pengangkatan Notaris. Penelitian ini adalah penilitian hukum normatif yang dianalisis menggunakan metode deskriptif kualitatif. Hasil penelitian ini menyimpulkan, pertama, Menteri Hukum dan Hak Asasi menerima laporan dari Majelis Kehormatan Notaris terkait banyaknya pemanggilan terhadap Notaris dan permintaan minuta akta oleh kepolisian sehingga diperlukan Ujian Pengangkatan Notaris. Kedua, Mahkamah Agung membatalkan Ujian Pengangkatan Notaris karena syarat kelulusan ujian pengangkatan Notaris bertentangan dengan peraturan perundang-undangan yang lebih tinggi. Ketiga, Menteri Hukum dan Hak Asasi Manusia mencabut ketentuan mengenai Ujian Pengangkatan Notaris dan mengganti dengan mekanisme lain yaitu Pelatihan Peningkatan Kualitas Jabatan Notaris (PPKJN).Kata-kata Kunci: Ujian Pengangkatan Notaris, Hak Uji Materiil, Syarat Pengangkatan Notaris